Warriors (Dialogue with the Emperor Qin's Warriors): an exhibition of 31 large-scale sculptures - John Atkin; Pick Keobandith (2016)
Twenty-eight artists from each EU country as well as three Chinese artists were invited by Qu Art to visit the world renowned Terracotta Warriors in Xian, China and to consider ways that these icons of the Emperor Qin’s reign could be reinterpreted within popular culture of the 21st Century. Each artist responded to the collection of warriors, acrobats and servants in a myriad of different ways, and in so doing reflected a discreet aspect of their own individual culture within the EU by making a sculpture that responded to this ancient collection. LUiL in conjunction with Here East, was the only venue for this seminal exhibition in the UK, and although this Group Show has been exhibited throughout China at a number of Tier One museums and galleries in order to widen the appreciation of European contemporary art practice to an audience that might not be familiar with the nuances of Western Art. These new audiences, familiar with the cultural significance of their own “Terracotta Warriors”, were able to view, first hand, the variety of ways that the selected Western Artists interpreted this iconic collection alongside the works of three contemporary Chinese artists. This was an opportunity to exhibit this body of work in London, connecting both the LU and LuL campuses through the auspices of Here East at Olympic Park. The significant impact of this exhibition, at a time of unique political flux because of BREXIT, demonstrates unique interpretations of this famous collection through contemporary art practice within the historical genre of cultural identity. However, this contemporary sculpture exhibition, which articulates contemporary ideas of EU-Sino relations through contemplation of the these historic antiquities is novel, as well as culturally important, bringing together connectivity between the EU and China at the twilight of the UK’s involvement in European identity. Here we can give visitors the opportunity to have face-to-face encounters with an actual “Dialogue with the Emperor Qins Warriors” through a modern-day adaptation of a historic collection, at time of momentous political change. The exhibition is also important because at its core the "Warriors" deal with notions of conflict and defense (the purpose of the Terracotta Warriors was to protect the Emperor in his afterlife) at a time of continuing war & conflict throughout the globe, and simultaneously at a time of historic reflection on The Great War.